A cell-permeant small molecule for the super-resolution imaging of the endoplasmic reticulum in live cells. Issue 15 (27th March 2019) - Sekhar, Adiki Raja; Mallik, Bhagaban; Kumar, Vimlesh; Sankar, Jeyaraman
Abstract : A simple BODIPY-based small molecule has been identified to selectively label the endoplasmic reticulum for high-resolution imaging with negligible cytotoxicity. Abstract : The endoplasmic reticulum (ER) constitutes about half of the total membrane of a eukaryotic cell, and defects in the ER have been shown to be linked with a variety of diseases. To investigate these underlying mechanisms in detail, the specific labelling of the ER for high-resolution long-term live-imaging can serve as an important tool. Here, we report the identification of a stimulated emission depletion (STED) microscopy-compatible BODIPY derivative (NH2 -BODIPY ) to selectively image the ER. In contrast to the conventional ER-Tracker™ dye, NH2 -BODIPY selectively labels the ER at a much lower concentration with no detectable cytotoxicity. Conventional imaging agents are often unstable under the intense light field used for STED microscopy, butNH2 -BODIPY is stable due to its robust structure and therefore it has the potential to be widely exploited for ER imaging.